Management of Spasticity After Traumatic Brain Injury in Children - Enslin, Johannes M. N.; Rohlwink, Ursula K.; Figaji, Anthony (Frontiers in Neurology, 2020)
Traumatic brain injury is a common cause of disability worldwide. In fact, trauma is the second most common cause of death and disability, still today. Traumatic brain injury affects nearly 475 000 children in the United States alone. Globally it is estimated that nearly 2 million people are affected by traumatic brain injuries every year. The mechanism of injury differs between countries in the developing world, where low velocity injuries and interpersonal violence dominates, and high-income countries where high velocity injuries are more common. Traumatic brain injury is not only associated with acute problems, but patients can suffer from longstanding consequences such as seizures, spasticity, cognitive and social issues, often long after the acute injury has resolved. Spasticity is common after traumatic brain injury in children and up to 38% of patients may develop spasticity in the first 12 months after cerebral injury from stroke or trauma. Management of spasticity in children after traumatic brain injury is often overlooked as there are more pressing issues to attend to in the early phase after injury. By the time the spasticity becomes a priority, often it is too late to make meaningful improvements without reverting to major corrective surgical techniques. There is also very little written on the topic of spasticity management after traumatic brain injury, especially in children. Most of the information we have is derived from stroke research. The focus of management strategies are largely medication use, physical therapy and other physical rehabilitative strategies, with surgical management techniques used for long-term refractory cases only. With this manuscript, the authors aim to review our current understanding of the pathophysiology and management options, as well as prevention, of spasticity after traumatic brain injury in children.